Chemical assessment and in vitro antioxidant capacity of Ficus carica latex - Oliveira, A.P. (2011)
Ficus species possess latex-like material within their vasculatures, affording protection and selfhealing from physical attacks. In this work, metabolite profiling was performed on Ficus carica latex. Volatiles profile was determined by HS-SPME/GC-IT-MS, with 34 compounds being identified, distributed by distinct chemical classes: 5 aldehydes, 7 alcohols, 1 ketone, 9 monoterpenes, 9 sesquiterpenes and 3 other compounds. Sesquiterpenes constituted the most abundant class in latex (ca. 91% of total identified compounds). Organic acids composition was also characterized, by HPLC-UV, and oxalic, citric, malic, quinic, shikimic and fumaric acids were determined. Malic and shikimic acids were present in higher amounts (ca. 26%, each). The antioxidant potential of this material was checked by distinct in vitro chemical assays. A concentration-dependent activity was noticed against DPPH, nitric oxide and superoxide radicals. Additionally, acetylcholinesterase inhibitory capacity was evaluated, but a weak effect was found.